Platelet-rich plasma versus steroid injection for subacromial impingement syndrome - Say, Ferhat; Gürler, Deniz; Bülbül, Murat (SAGE Publications Inc, 2016)
Purpose. To compare the 6-week and 6-month outcome in 60 patients who received a single-dose injection of platelet-rich plasma (PRP) or steroid for subacromial impingement syndrome (SIS). Methods. 22 men and 38 women (mean age, 49.7 years) opted to receive a single-dose injection of PRP (n=30) or steroid (n=30) for SIS that had not responded to conservative treatment for >3 months. The PRP or a mixture of 1 ml 40 mg methylprednisolone and 8 ml prilocaine was administered via a dorsolateral approach through the interval just beneath the dorsal acromial edge. Both groups were instructed to perform standard rotator cuff stretching and strengthening exercises for 6 weeks. The use of non-steroid anti-inflammatory drugs was prohibited. Patients were evaluated before and 6 weeks and 6 months after treatment using the Constant score, visual analogue scale (VAS) for pain, and range of motion (ROM) of the shoulder. Results. No local or systemic complication occurred. Improvement in the Constant score and VAS for pain at week 6 and month 6 was significantly better following steroid than PRP injection. The difference in the Constant score was greater than the mean clinically important difference of 10.4. Nonetheless, the 2 groups were comparable for improvement in ROM of the shoulder. Conclusion. Steroid injection was more effective than PRP injection for treatment of SIS in terms of the Constant score and VAS for pain at 6 weeks and 6 months.
Keywords: Platelet-Rich Plasma; Shoulder Impingement Syndrome; Steroids